ANALISIS PERMASALAHAN PEMBIAYAAN MUDHARABAH SERTA SOLUSINYA PADA BANK SYARIAH DI INDONESIA - Laura Aprilia Putri; Alvianda Nurliawan; Kania Esfandiari Fauziah; Muhammad Irsyad Syamil; Tri Setiady (Universitas Wiralodra, 2025)
Mudharabah financing is a financing product that is run based on the principle of profit sharing in the sharia banking system, where the sharia bank is the shahibul maal (capital owner) and the customer is the mudharib (business manager). In Indonesia, mudharabah financing has shown significant development as an alternative financing that complies with sharia principles. However, there are various problems that hamper the effectiveness of this financing product. This analysis aims to identify and analyze problems that occur in mudharabah financing in Indonesian sharia banks, as well as provide recommendations for solving them.